Central mechanisms of muscle tone regulation: implications for pain and performance - Cacciatore, Timothy W.; Anderson, David I.; Cohen, Rajal G. (Frontiers in Neuroscience, 2024)
Muscle tone represents a foundational property of the motor system with the potential to impact musculoskeletal pain and motor performance. Muscle tone is involuntary, dynamically adaptive, interconnected across the body, sensitive to postural demands, and distinct from voluntary control. Research has historically focused on pathological tone, peripheral regulation, and contributions from passive tissues, without consideration of the neural regulation of active tone and its consequences, particularly for neurologically healthy individuals. Indeed, simplistic models based on the stretch reflex, which neglect the central regulation of tone, are still perpetuated today. Recent advances regarding tone are dispersed across different literatures, including animal physiology, pain science, motor control, neurology, and child development. This paper brings together diverse areas of research to construct a conceptual model of the neuroscience underlying active muscle tone. It highlights how multiple tonic drive networks tune the excitability of complex spinal feedback circuits in concert with various sources of sensory feedback and in relation to postural demands, gravity, and arousal levels. The paper also reveals how tonic muscle activity and excitability are disrupted in people with musculoskeletal pain and how tone disorders can lead to marked pain and motor impairment. The paper presents evidence that integrative somatic methods address the central regulation of tone and discusses potential mechanisms and implications for tone rehabilitation to improve pain and performance.